Portraits socio-sanitaires des communautés francophones de l'Ontario | Demographic and health profiles of Ontario's Francophone communities - Gagnon-Arpin, Isabelle; Sedigh, Golnaz; Bouchard, Louise (Alliance des réseaux ontariens de santé en français, 2011)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)